2003
DOI: 10.1128/aem.69.4.2023-2031.2003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antifungal and Antioomycete Activities of Aerugine Produced by Pseudomonas fluorescens Strain MM-B16

Abstract: The bacterial strain MM-B16, which showed strong antifungal and antioomycete activity against some plant pathogens, was isolated from a mountain forest soil in Korea. Based on the physiological and biochemical characteristics and 16S ribosomal DNA sequence analysis, the bacterial strain MM-B16 was identical to Pseudomonas fluorescens. An antibiotic active against Colletotrichum orbiculare and Phytophthora capsici in vitro and in vivo was isolated from the culture filtrates of P. fluorescens strain MM-B16 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 53 publications
0
35
0
2
Order By: Relevance
“…1998) have been described as producers of effective biological control agents antagonistic to many fungal phytopathogens. However, data pertaining to the antagonistic activity of bacteria against M. grisea , a potent rice pathogen, are still restricted to only a few strains of Pseudomonas (Lee et al. 2003), Streptomyces (Gomes et al.…”
Section: Introductionmentioning
confidence: 99%
“…1998) have been described as producers of effective biological control agents antagonistic to many fungal phytopathogens. However, data pertaining to the antagonistic activity of bacteria against M. grisea , a potent rice pathogen, are still restricted to only a few strains of Pseudomonas (Lee et al. 2003), Streptomyces (Gomes et al.…”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa ID 4365 produced PCA which showed inhibitory activities against Aspergillus -niger NCIM1025, Fusarium oxysporum NCIM1008, Sclerotium rolfsii NCIM 1084, Colletotrichum falcatum and several other phytopathogens (Makarand et al, 2007). Lee et al (2003) was also reported that minimal inhibitory concentration of PCA produced by this strain for S. rolfsii NCIM 1084 was found to be 29 mg/L. The inhibitory action of pyocyanin was proposed that, during respiration, pyocyanin becomes reduced and univalently reduces oxygen to the toxic superoxide radical.…”
Section: Discussionmentioning
confidence: 99%
“…1), was purified and chemically characterized from the culture filtrate of the actinomycete strain VK‐A9 by analysing NMR and MS spectral data 13. Various antifungal compounds such as manumycin‐type antibiotic SW‐B,14 fistupyrone,15 phenazine‐1‐carboxylic acid,16 aerugine,17 A90931a18 and staurosporine19 isolated from soil microorganisms have been demonstrated to have potent antifungal or antioomycete activity for the control of economically important plant diseases.…”
Section: Introductionmentioning
confidence: 99%